Pertumbuhan dan hasil sawi pagoda yang dipupuk dengan berbagai kombinasi sumber kompos dan jenis kompos - Sari, Shabilla Amartiya; Nur, Tri Putri; Gofar, Nuni - (Jurnal AGRO, 2023)
Tatsoi is a popular vegetable in the community but has not been widely cultivated in South Sumatra. Compost tea is a type of liquid organic fertilizer that is easy to make and can increase plant growth and production. This study aimed to determine the best combination of source and type of compost to increase the tatsoi growth and yield. The research was conducted on May-August 2023 at the Experimental Garden of Faculty of Agriculture, Sriwijaya University. The research consisted of 2 factors designed in a Randomized Complete Factorial Design. The first factor was the source of compost, namely cow manure, chicken manure, goat manure, vermicompost, and oil palm empty fruit bunch compost. The second factor was the type of compost: solid compost, aerated compost tea 1:5 (b/v), aerated compost tea 1:10 (b/v), non-aerated compost tea 1:5 (b/v), and non-aerated compost tea 1:10 (b/v). Based on the research, the application of various types and sources of compost interacted significantly on the growth and yield of tatsoi, except on the number of leaves and root crown ratio variables. The combination of aerated chicken manure compost tea treatment with a ratio of 1:5 (b:v) was the best treatment in the cultivation of tatsoi in soil of lebak swamp.ABSTRAKSawi pagoda merupakan salah satu sayuran yang populer di masyarakat namun belum banyak dibudidayakan di Sumatera Selatan. Teh kompos adalah jenis pupuk organik cair yang mudah dibuat serta mampu meningkatkan pertumbuhan dan hasil tanaman. Penelitian ini bertujuan untuk mengetahui kombinasi terbaik sumber dan jenis kompos untuk meningkatkan pertumbuhan dan produksi sawi pagoda. Penelitian dilaksanakan pada bulan Mei-Agustus 2023 di Kebun Percobaan FP Universitas Sriwijaya. Penelitian terdiri dari dua faktor dalan Rancangan Acak Lengkap Faktorial (RALF). Faktor pertama adalah sumber kompos yaitu pupuk kandang sapi, pupuk kandang ayam, pupuk kandang kambing, vermikompos, dan kompos tandan kosong kelapa sawit. Faktor kedua adalah jenis kompos yaitu: kompos padat, teh kompos aerasi perbandingan 1:5 (b/v), teh kompos aerasi perbandingan 1:10 (b/v), teh kompos tanpa aerasi perbandingan 1:5 (b/v), dan teh kompos tanpa aerasi perbandingan 1:10 (b/v). Berdasarkan hasil penelitian, aplikasi berbagai jenis dan sumber kompos berinteraksi secara nyata terhadap pertumbuhan dan hasil sawi pagoda, kecuali pada peubah jumlah daun dan nisbah tajuk akar. Kombinasi perlakuan teh kompos kotoran ayam yang diaerasi dengan perbandingan 1:5 (b:v) merupakan perlakuan terbaik dalam budidaya tanaman sawi pagoda pada tanah asal rawa lebak.